The change of the meaning of coffee shop into a space of sociocultural entity (A case study of the community in Makassar City) - Hakim, Maksud (Kasetsart Journal of Social Sciences, 2021)
This study aims to investigate the process of change in the meaning of coffee shop from traditional to modern, how the meaning of coffee shop changes into a space of sociocultural entity and the change of the meaning of coffee shop into an effective instrument of political socialization. This is a case study using a qualitative descriptive approach and the informants were selected using purposive sampling technique. This study also uses a naturalistic (qualitative) paradigm approach to analyze and construct the change of the meaning of coffee shop into a space of sociocultural entity in Makassar municipality, South Sulawesi. The data analysis was done through data reduction focused on selection, simplification, abstraction and transformation of raw data from field notes, followed by data display and conclusion drawing. The results of this study indicate that the change in the meaning of coffee shop from traditional to modern is characterized by its development into a public space equipped with various facilities and information sources such as television, newspapers, and internet networks to meet the needs and satisfaction of the visitors. Coffee shop has become a socio-cultural entity in developing interaction and interrelation patterns as a unifier in association without regard to race, religion and so on, and it has been used as a means of political discussion and self-image, both formally and informally, of work program socialization with political figures or authorities and of effectively extracting actual information from visitors.